(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Abstract : In recent years, the pace of people’s life has accelerated and the pressure has increased, resulting in anincrease in the number of abandoned pets. Pet abandonment is a heartbreaking issue that affects animalsworldwide. When owners abandon their pets, it can lead to immediate and long-term consequences for theseinnocent creatures. Abandoned animals often suffer from malnutrition, exposure to harsh weather, and lackofmedicalcare.So Pet Adoption System project is to introduced to handle this aboned pets. This pet adoption website is acomprehensive solution for connecting pets in need of homes with loving adopters. By combining user friendly design,detailedpetprofiles,astreamlinedadoptionprocess,andeducationalresources,theplatformsignificantlyenhancesthechancesof finding forever homes for countless animals.